Assessing preschool teachers' challenges and needs for creativity in STEM education / Muhammad Syawal Amran ... [et al.] - Amran, Muhammad Syawal; Abu Bakar, Kamariah; Surat, Shahlan; Mahmud, Siti Nur Diyana; Mohd Shafie, Amirul Anwar (Universiti Teknologi MARA, 2021)
Creativity in teaching is important in order to ensure children are engaged in learning Science, Technology, Engineering and Mathematics (STEM). However, previous research has claimed creativity in learning STEM for children is not adequately supported by teacher in classroom due to the lack of preparation, content knowledge and skills. This study aims to assess the needs and challenges of promoting creativity in STEM education. In this study, preschool teachers (n= 22) were interviewed as they are the key informants who are involved in STEM education. The semi-structured interviews were analysed using qualitative content analysis and were qualitatively coded. Results illustrate that there are several distinctive themes identified as described by the participants when discussing the needs and challenges of implementing integrated creativity skill in STEM education as well as the support that would be most helpful in overcoming them. The results highlighted a huge gap between creativity knowledge and the implementation of creativity in STEM education. Participants also provided specific support needed to integrate creativity in STEM education. Preliminary findings suggest that many teachers are interested in integrating creativity skills in STEM education. This research sheds light on the needs and challenges for professional pre-school teachers by providing them pedagogical module as well as professional training to promote creativity in teaching STEM.